2014
DOI: 10.1111/apt.12744
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of scoring systems and outcome of patients admitted to a liver intensive care unit of a tertiary referral centre with severe variceal bleeding

Abstract: Summary Background Acute variceal haemorrhage (AVH) is associated with significant mortality. Aims To determine outcome and factors associated with hospital mortality (HM) in patients with AVH admitted to intensive care unit (ICU) and to compare outcomes of patients requiring transfer to a tertiary ICU (transfer group, TG) to a local in‐patient group (LG). Methods A retrospective study of all adult patients (N = 177) admitted to ICU with AVH from 2000–2008 was performed. Results Median age was 48 years (16–80)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 66 publications
(119 reference statements)
4
19
1
Order By: Relevance
“…Our patient population had probably more severe liver disease than in the previous trial for several reasons: (i) we did not exclude patients with a previous history of variceal bleeding or with portal vein thrombosis; (ii) a majority of our patients were classified Child–Pugh C (77.4%) compared to ≈50% in the previous study; (iii) the mean MELD score was higher in our cohort (21 vs. 15); and a recent study has suggested that mortality is highly correlated with the MELD score . These results were confirmed in another paper, suggesting that the MELD score was a good predictive model of mortality in patients with severe variceal bleeding admitted to a hepatology intensive care unit in a tertiary referral centre . Moreover, our study was limited because the control group included historical retrospectively enrolled patients.…”
Section: Discussionsupporting
confidence: 65%
“…Our patient population had probably more severe liver disease than in the previous trial for several reasons: (i) we did not exclude patients with a previous history of variceal bleeding or with portal vein thrombosis; (ii) a majority of our patients were classified Child–Pugh C (77.4%) compared to ≈50% in the previous study; (iii) the mean MELD score was higher in our cohort (21 vs. 15); and a recent study has suggested that mortality is highly correlated with the MELD score . These results were confirmed in another paper, suggesting that the MELD score was a good predictive model of mortality in patients with severe variceal bleeding admitted to a hepatology intensive care unit in a tertiary referral centre . Moreover, our study was limited because the control group included historical retrospectively enrolled patients.…”
Section: Discussionsupporting
confidence: 65%
“…CTP-Cr score had the highest prognostic capability followed by CTP scores. Our results are in contrary with, Al-Freah et al 44 who found that MELD had the best performance as the best liver prognostic model but did not significantly differ from other ICU scoring models as predictors of outcome. Peng et al in 2015 45 found that both scoring systems; CTP and MELD, had good discriminative abilities for the IHM of acute UGIB in liver cirrhosis, and that the AUROC for MELD score might be slightly supe rior to that for Child-Pugh score, but with no statistically significant difference.…”
Section: Articlecontrasting
confidence: 99%
“…Increased requirement of blood /blood product transfusion was significantly associated with mortality, this finding correlates with that of Al-Freah et al [15]. Who reported that there was a 7% rise in hospital mortality with every unit increase in Packed RBCs transfusion on the day of admission.…”
Section: Discussionsupporting
confidence: 84%
“…However, this does not correlate with Afessa and Kubilis [21], who compared the prognostic performances of APACHE II and Child-Pugh score in 111 cirrhotic patients hospitalized for upper GI bleeding and did not find significant differences between the two scoring systems. In a single centre cohort of ICU admitted patients presented with acute upper gastrointestinal bleeding from varices Al-Freah et al [15] found that MELD has the best performance as it could be best liver prognostic models and not significantly different from other ICU scoring models as predictors of outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation